Superficial acral fibromyxoma: A case report - Yue ZHANG; Jinru SONG; Ruoyun LIU; Liuhong LIU; Renliang HE; Bin YANG (Pifu-xingbing zhenliaoxue zazhi, 2024)
We report a case of subungual superficial acral fibromyxoma in a 74-year-old woman, who had a subungual neoplasm on the right big toe for 2 months. Dermatological examination revealed a red tumor about 3.0 cm×2.0 cm×1.0 cm in size at the nail bed of the right big toenail and onychomadesis. Ultrasound examination of the tumor showed a hypoechoic mass about 21 mm×20 mm in size with an uneven internal echoes of mixed cysts and solids under the right big toe. Digital Radiography of the right foot showed swollen soft tissue of the right big toe, with no changes in bone. Histological changes included epidermal hyperkeratosis and parakeratosis, and partial thickening of spinous layers along with edema of the superficial dermis. There were increases in small blood vessels, fibrous tissue, spindle cells and stellate cells, in addition to perivascular infiltrates of lymphocytes. Alcian blue staining was positive. Immunohistochemistry showed positive for CD34 and Vimentin, and negative for S-100, Desmin, Actin, CD31 and HHV-8. Diagnosis was superficial acral fibromyxoma. The nail bed was healed well after surgical removal of the tumor, and no recurrence was observed.